2006
DOI: 10.1089/pho.2006.24.616
|View full text |Cite
|
Sign up to set email alerts
|

Biomodulative Effects of Polarized Light on the Healing of Cutaneous Wounds on Nourished and Undernourished Wistar Rats

Abstract: It is concluded that nutritional status influenced the progression of the healing process as well as the quality of the healed tissue, and that the use of polarized light resulted in a positive biomodulatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 25 publications
6
38
0
11
Order By: Relevance
“…These reports can be separated into two broad groups depending on whether the animals used were normal, or whether they had been manipulated in some way to depress wound healing. These manipulations employed to impair normal wound healing include diabetes [26], ionizing radiation [27], treatment with corticosteroids [28], or malnourishment [29]. Indeed, it has been asserted that normal healthy rodents may not be a suitable model for studying LLLT effects on wound healing [30].…”
Section: Discussionmentioning
confidence: 99%
“…These reports can be separated into two broad groups depending on whether the animals used were normal, or whether they had been manipulated in some way to depress wound healing. These manipulations employed to impair normal wound healing include diabetes [26], ionizing radiation [27], treatment with corticosteroids [28], or malnourishment [29]. Indeed, it has been asserted that normal healthy rodents may not be a suitable model for studying LLLT effects on wound healing [30].…”
Section: Discussionmentioning
confidence: 99%
“…Laser therapy is used in many biomedical sciences to promote tissue regeneration (Mester, Mester et al 1985;Karu 1999). Many studies involving the low-level laser therapy have shown that the healing process is enhanced by such therapy (Enwemeka 1988;Rochkind, Rousso et al 1989;Nemeth 1993;Grossman, Schneid et al 1998;O'Brien, Li et al 1998;Lilge, Tierney et al 2000;Maegawa, Itoh et al 2000;Schlager, Kronberger et al 2000;Sommer, Pinheiro et al 2001;Wong-Riley, Bai et al 2001; do Nascimento, Pinheiro et al 2004;Eells, Wong-Riley et al 2004;Pinheiro, Meireles et al 2004;Hawkins, Houreld et al 2005). In Table 5 we show the results of LLLT therapy in the pilot study of 38 children with jSpA diagnosed based on both ESSG and ILAR criteria, which we treated, in addition to standard NSAID therapy, with LLLT (Harjacek and Lamot 2008).…”
Section: Treatment Of Jspamentioning
confidence: 99%
“…In agree ment with reports publis hed in the lite ra tu re, the expe ri men tal induc tion of maras mus in rats was con fir med by their weight and by the cli ni cal signs pre sen ted by the ani mals. 2,6,8,11,12 With res pect to serum albu min levels, the results were simi lar in the well-nou ris hed and mal nou ris hed groups after 60 days of fol low-up, pos sibly due to the slow, bela ted reduc tion in albu min levels in maras mus. 2,6 Similar results were found with the gela tin model in which a diet con tai ning low qua lity pro tein was used.…”
Section: Discussionmentioning
confidence: 85%
“…Serum albu min levels remain prac ti cally unchan ged, with decrea ses only being detec ted at a later stage. 4,[6][7][8]12 In addi tion to this type of mal nu tri tion, ano ther type may be trig ge red when the die tary inta ke of speci fic nutrients such as pro tein is insuf fi cient or when inta ke is based on poor qua lity pro tein such as gelatin. Gelatin is a dena tu red col la gen, the amino acid com po si tion of which con sists of a high con cen tra tion of glyci ne, pro li ne and hydroxy pro li ne asso cia ted with a low or negli gi ble con cen tra tion of tyro si ne, trypto pha ne, iso leu ci ne, cysti ne and his ti di ne.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation